Pengaruh Program Pengembangan Usaha Agribisnis Pedesaa (PUAP) Terhadap Pendapaatan Petani Studi Kasus di Desa Mangeloreng Kecamatan Bantimurung Kabupaten Maros - miranda miranda; Abd. Asis Pata; Andi Nur Imran (Jurnal Agribis, 2023)
The income of rice farmers is lower because there are still many farmers who do not have farming tools and the very high price of fertilizer seeds makes farmers spend more on sales and costs related to PUAP and after PUA. This research was conducted in Mangeloreng village, Bantimurung sub-district, Maros district, where this research was carried out from January to March 2022. The method used was the proportionate stratified random sampling method, using a total population of 170, 15% were taken, namely 26 farmers.